2014
DOI: 10.1017/jrr.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Quality, Work-Family Stress, and Mental Health Among Australian Male Mining Industry Employees

Abstract: Australia is one of the world's foremost mining nations. While the economic and employment benefits of the mining industry are well documented, potentially negative aspects of mining industry employment are less understood. It has been suggested that mining industry workers may be more likely than workers in other occupations to experience relationship problems and work-family stress, but there is very little empirical study examining this proposal. Data from the nationally representative Household, Income, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Consistent with previous studies, 2 , 7 , 8 the remoteness of the mining lifestyle was significantly associated with high psychological distress. Most notably, stress associated with the stigma attached to mental health problems was the strongest predictor of high psychological distress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies, 2 , 7 , 8 the remoteness of the mining lifestyle was significantly associated with high psychological distress. Most notably, stress associated with the stigma attached to mental health problems was the strongest predictor of high psychological distress.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4][5][6] In particular, FIFO (fly in/fly out) and DIDO (drive in/drive out) employment arrangements have become more common in recent years, accompanied by a range of lifestyle stressors, such as motelling (hotbedding), compressed rosters, and social isolation. 6,7 These arrangements can increase relationship and family strains, 8,9 sleep disturbances, 5,10 and risky behaviour, such as excessive drinking. 2,11 Male predominance in the resource and mining workforce (88%) 12 and their low rates of help-seeking have motivated research into the risks of mental ill health in the FIFO population.…”
mentioning
confidence: 99%
“…For instance, a Canadian study involving mining communities identified increases in mental health problems that correlated with a deteriorating economic climate [52]. Financial stress has also been connected to poor mental and emotional wellbeing, and greater family stress [53].…”
Section: Discussionmentioning
confidence: 99%
“…Such issues include the typical preponderance of male workers, which tends to promote a macho culture with heightened levels of bullying and stigmatization of mental illness (Bowers et al., ). Other potential factors include relationship difficulties resulting from regular partner absence, substance abuse, impaired health service access, isolation, loneliness, and lack of social support (House of Representatives Standing Committee on Regional Australia., ; Joyce, Tomlin, Somerford, & Weeramanthri, ; McPhedran & De Leo, ; Torkington, Larkins, & Gupta, ; Tynan et al., ).…”
Section: Introductionmentioning
confidence: 99%